2015
DOI: 10.1016/j.envres.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposure to chlordecone, thyroid hormone status and neurodevelopment in infants: The Timoun cohort study in Guadeloupe (French West Indies)

Abstract: Background: Perinatal exposure to endocrine-disrupting chemicals may affect thyroid hormones homeostasis and impair brain development. Chlordecone, an organochlorine insecticide widely used in the French West Indies has known estrogenic and progestin properties, but no data is available, human or animal, on its action on thyroid hormone system. Objectives: Our aim was to evaluate the impact of perinatal exposure to chlordecone on the thyroid hormone system of a sample of infants from the Timoun mother-child co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 39 publications
(49 reference statements)
0
29
0
1
Order By: Relevance
“…In 2015, a longitudinal birth-cohort (n = 111) study in Guadeloupe investigated the effects of prenatal and postnatal exposure during breastfeeding. The authors reported that prenatal exposure was associated with increased levels of TSH in boys, while postnatal exposure determined at 3 months was associated with decreased FT3 levels in both genders, and FT4 levels in girls (80).…”
Section: Epidemiological Evidence Of Thyroid Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, a longitudinal birth-cohort (n = 111) study in Guadeloupe investigated the effects of prenatal and postnatal exposure during breastfeeding. The authors reported that prenatal exposure was associated with increased levels of TSH in boys, while postnatal exposure determined at 3 months was associated with decreased FT3 levels in both genders, and FT4 levels in girls (80).…”
Section: Epidemiological Evidence Of Thyroid Disruptionmentioning
confidence: 99%
“…Because DDT, HCB, and other OCPs have been associated with impaired neurodevelopment and neurocognition in infants and children (60)(61)(62)(63)(64)(65)(66)(67)(68)(69), numerous epidemiological studies have investigated whether these adverse effects could be mediated, at least in part, by disruption of the HPT axis in either pregnant women or newborns (70)(71)(72)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81). An overview of the epidemiological organochlorine studies can be found in Table 1. A Canadian birth-cohort study (n = 101) studied several OCs in pregnant women and observed that p,p ′ -DDE, the main metabolite of DDT, HCB and a constituent of chlordane were negatively associated with total T3 (TT3) levels, and β-HCH with FT4 (78).…”
Section: Epidemiological Evidence Of Thyroid Disruptionmentioning
confidence: 99%
“…In humans, recent epidemiological and toxicological studies have demonstrated that chlordecone is a reproductive and developmental toxicant, an endocrine-disrupting chemical and a neurotoxic. It is also consistently associated with an increase in the risk of prostate cancer (Multigner et al, 2010, 2016; Cordier et al, 2015; Emeville et al, 2015). Chlordecone persists in the environment (Cabidoche et al, 2009; Fernández-Bayo et al, 2013; Devault et al, 2016), and since it bioaccumulates as it moves through the food chain, it was listed in the Persistent Organic Pollutants (POPs) prohibition list of the Stockholm Convention (UNEP/POPS/POPRC.1/INF/6, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, CLD was added to the list of persistent organic pollutants in the Stockholm Convention, banning its production and use worldwide. Studies suggest exposure to CLD may be linked to higher occurrence of prostate cancer and to impaired cognitive and motor development in young children [1,[12][13][14]. Watershed modelling predicts that CLD will remain in soils for decades or even centuries because of its stability and affinity for soil organic matter, providing a long term source of contamination to the aquatic environment [2].…”
Section: Introductionmentioning
confidence: 99%